1990
DOI: 10.1002/ls.3010020403
|View full text |Cite
|
Sign up to set email alerts
|

Ashless antioxidants, copper deactivators and corrosion inhibitors: Their use in lubricating oils

Abstract: This paper reviews the use of copper deactivators and iron corrosion inhibitors in lubricating oils. The auto‐oxidation process is described in terms of initiation and chain propagation, branching and termination, and the primary and secondary oxidation inhibitors are described. Copper deactivators and corrosion inhibitors nature and action are discussed, and the paper also examines the applications for these additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…It is well documented in literature that benzotriazole is a good corrosion inhibitor for the protection of copper in aqueous environments, so an OBT was chosen for study to see if the same was true in oil‐based media. Dimercaptothiadiazole was chosen as it is a common corrosion inhibitor used in lubricating fluids …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented in literature that benzotriazole is a good corrosion inhibitor for the protection of copper in aqueous environments, so an OBT was chosen for study to see if the same was true in oil‐based media. Dimercaptothiadiazole was chosen as it is a common corrosion inhibitor used in lubricating fluids …”
Section: Methodsmentioning
confidence: 99%
“…Dimercaptothiadiazole was chosen as it is a common corrosion inhibitor used in lubricating fluids. [9][10][11][12][13] Copper coupons of 99.95% purity, provided by Metaspec, USA, were precut into approximately 1-cm lengths. Each test used 1 copper coupon per beaker.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been reported that the degradation is caused by an autocatalytic reaction, the degradation mechanism of turbine oil is very complicated [25][26][27]. Air and water combined with localized high temperatures or static electricity are the main causes of oil oxidation and degradation [28].…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…The mechanism of auto-oxidation of hydrocarbon lubricating oils is a well-researched and established subject (Hamblin et al 1989, Mayo 1968. It is generally accepted that it follows the mechanism for low molecular weight saturated hydrocarbons in the liquid phase, i.e., it is a free radical chain mechanism consisting of the following steps:…”
Section: Free Radicalsmentioning
confidence: 99%
“…The mechanisms of initiation and chain propagation (Hamblin et al 1989) for the auto-oxidation of lubricating oils are assumed to be very similar, for both hydrocarbon-based and polyol esterbased lubricating oils: As was mentioned before reaction (7) is stress induced, aided by catalysts and gets the chain reaction started, while (8) is the oxygen absorbing step, which results in the formation and accumulation of the hydro peroxides ROOH (9) and perhaps their accumulation. Reaction (8) is faster than reaction (7).…”
Section: Initiation Chain Propagation Chain Branching Chain Terminationmentioning
confidence: 99%